2021
DOI: 10.1007/s11033-021-06165-8
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and annotation of the endangered wild buffalo (Bubalus arnee) mitogenome for taxonomic assessment

Abstract: The wild water buffalo (Bubalus arnee) is one of the most endangered and least studied large bovid in the Indian subcontinent. India retains 90% of the global population as two fragmented populations in Assam and Chhattisgarh, both threatened by habitat loss and degradation, hunting, disease from livestock, and hybridization with the domestic buffalos.For the first time, we sequenced the 16,357 bp long mitogenome of pure wild water buffalo from both populations. The annotated genes included 13 protein-coding g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Historical persecutions and domestication of the wild buffaloes have led to their extinction from their former range. Using samples of wild and domestic buffaloes from across their range, our results strengthen earlier studies that indicated northeast and central Indian wild buffaloes to be genetically similar compared to many domesticated water buffaloes within India (Mishra & Gaur 2019; Pacha et al 2021). The close genetic association of wild buffaloes from northeast and central India based on mitochondrial data is suggestive of common maternal lineages of these populations.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Historical persecutions and domestication of the wild buffaloes have led to their extinction from their former range. Using samples of wild and domestic buffaloes from across their range, our results strengthen earlier studies that indicated northeast and central Indian wild buffaloes to be genetically similar compared to many domesticated water buffaloes within India (Mishra & Gaur 2019; Pacha et al 2021). The close genetic association of wild buffaloes from northeast and central India based on mitochondrial data is suggestive of common maternal lineages of these populations.…”
Section: Discussionsupporting
confidence: 86%
“…Megaherbivores were ubiquitous and likely abundant across terrestrial ecosystems until very recently, when humans selectively eliminated them at continental scales (Surovell et al 2005;Sandom et al 2014;Dembitzer et al 2022) a process that is still widely ongoing (Chase et al 2016). Megaherbivores are keystone species as they influence ecosystems by modifying species composition, nutrient cycling, primary productivity, fire, and water regimes (Owen-Smith 1988). Increasingly, research is linking their decline (Smith et al 2018) to a cascade of co-extinctions (Keesing & Young 2014), trophic degradation (Estes et al 2011), altered fire regimes (Rule et al 2012;Karp et al 2021), an increase in invasive species (Mungi et al 2023b), and a lasting anthropogenic impact on the biosphere (Malhi et al 2016;Enquist et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Upon scrutiny, it was observed that both Hangul mitogenomes from GenBank were identical and therefore only one of the sequences ( ) was used in all analyses. Three sequences from Bovidae group: wild buffalo ( Bubalus arnee ) ( Pacha et al, 2021 ), Indian gaur ( Bos gaurus ) ( Hassanin et al, 2012 ) and Cape buffalo ( Boselaphus tragocamelus ) ( Hassanin et al, 2012 ) were used as outgroup in this analysis. MEGA v7 was used to estimate inter-sequence mean pairwise genetic distance ( Kumar, Stecher & Tamura, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the taxonomic status of the domestic water buffalo types is still debated and they were considered as two subspecies by some authors [10,11] or different species by others [9,[13][14][15]. sequence [16], we reconstructed the phylogenetic relationship between the three water buffalo types and the other members of genus Bubalus based on the whole mitogenome sequence. The phylogenetic tree included: lowland anoa (Bubalus depressicornis), mountain anoa (Bubalus quarlesi) in addition to the wild, river and swamp water buffalo types.…”
Section: Introductionmentioning
confidence: 99%